The grand strategy of classical Sparta the Persian challenge - Rahe, Paul Anthony (The Yale library of military history, 2015)
Rahe provides a fascinating, detailed picture of life in Sparta circa 480 B.C., revealing how the Spartans' form of government and the regimen to which they subjected themselves instilled within them the pride, confidence, discipline, and discernment necessary to forge an alliance that would stand firm against a great empire, driven by religious fervor, that held sway over two-fifths of the human race.